(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract. One of the problems that must be solved is the occurrence of tooth-jaw anomalies in the pathology of children's tooth-jaw system. From the first days of life, early orthodontic treatment for children with facial and jaw defects is a preparatory stage in the pre-operative period, aimed at creating favorable conditions for further surgical intervention. In early orthodontic treatment procedures , the jaw dimensions, the position of the jaws in relation to the base of the skull, the ratio of dental arches and the comparative diagnosis of tooth position defects are of great importance, and this article is about the solution of this issue.